2010
DOI: 10.1111/j.1523-1739.2009.01377.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Urbanization for Artisanal Parrotfish Fisheries in the Western Solomon Islands

Abstract: Increasing migration into urbanized centers in the Solomon Islands poses a great threat to adjacent coral reef fisheries because of negative effects on the fisheries and because it further erodes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 34 publications
1
58
0
Order By: Relevance
“…In two studies [50], similar performance with open access was reported in the absence of monitoring and high resource use pressure. Overall, regime characteristics were not broadly discussed, and we noted only three studies [51,55,56] that discussed positive regime characteristics.…”
Section: Results From Fisheries Resource Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In two studies [50], similar performance with open access was reported in the absence of monitoring and high resource use pressure. Overall, regime characteristics were not broadly discussed, and we noted only three studies [51,55,56] that discussed positive regime characteristics.…”
Section: Results From Fisheries Resource Systemsmentioning
confidence: 99%
“…Only 16 studies reported enough baseline data [36,40,41,44,46,47,51,55,56] and these were classified into poor, fair and good conditions (Fig. 12).…”
Section: Resource Baseline Condition As a Contextual Factormentioning
confidence: 99%
“…In some cases, communities will harvest fish from these areas to provide food for culturally important occasions (Bartlett et al, 2009). Empirical studies suggest that these 'hybrid' systems are having tangible conservation benefits; when compared to nearby areas open to fishing, they have more than three times the biomass of fish vulnerable to overfishing inside periodically harvested areas in Vanuatu and two times the amount of herbivorous parrotfish in some community-based closures in Solomon Islands (Aswani and Sabetain, 2010;Bartlett et al, 2009). Importantly, the rules-in-use developed by these 'hybrid' systems are more likely to reflect local social, economic, and cultural conditions than those devised by technocrats in far away capital cities.…”
Section: Property Rights and Strong Local Institutionsmentioning
confidence: 98%
“…Benefits of these customary practices include increases in fisheries yields (McClanahan et al, 1997), target species biomass (Cinner et al, 2005a, b) and abundance (Aswani & Sabetian, 2010). Important ecosystem processes, such as herbivory , and metrics of ecosystem health, such as coral cover are often higher in areas under customary management (Baird et al, 2005), Integrating these customary systems with contemporary management practices (e.g., spatially defined marine protected areas) continues to be an area of active research (Johannes, 2002;Aswani et al, 2007) with these alternate forms of marine resource management increasingly being advocated .…”
Section: Introductionmentioning
confidence: 99%